2015
DOI: 10.1007/s00428-015-1887-4
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma ex-pleomorphic adenoma of the salivary glands has a high risk of progression when the tumor invades more than 2.5 mm beyond the capsule of the residual pleomorphic adenoma

Abstract: Carcinoma ex-pleomorphic adenoma (CPA) is subclassified based on the extent of penetration of the malignant component beyond the fibrous capsule of the pre-existing pleomorphic adenoma (PA). These subclasses are considered to be prognostically significant since the non-invasive/minimally invasive groups have an excellent outcome. Nevertheless, there is no consensus as to the cutoff value to distinguish between minimal and wide invasion, even though the 2005 WHO classification defines 1.5 mm as cutoff. The obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…For instance, carcinoma ex PA (CPA) is considered a highgrade tumor and, although the carcinomatous component is often of a high-grade subtype (salivary duct carcinoma [SDC] or adenocarcinoma NOS), low-grade morphologies can also be present. Furthermore, most series have shown that it is the extent of invasion of the carcinomatous component into the surrounding tissue that has the strongest prognostic impact; intracapsular/minimally invasive tumors, irrespectively of the grade of the malignant component, have a favorable outcome [11][12][13][14]. The only neoplasms that are consistently graded in current practice are adenoid cystic carcinomas (AdCC), based on the growth pattern, mucoepidermoid carcinoma (MEC), with a combination of growth pattern and cytomorphological findings, and adenocarcinomas NOS, based on the degree of cellular atypia [1,8].…”
Section: Histological Gradingmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, carcinoma ex PA (CPA) is considered a highgrade tumor and, although the carcinomatous component is often of a high-grade subtype (salivary duct carcinoma [SDC] or adenocarcinoma NOS), low-grade morphologies can also be present. Furthermore, most series have shown that it is the extent of invasion of the carcinomatous component into the surrounding tissue that has the strongest prognostic impact; intracapsular/minimally invasive tumors, irrespectively of the grade of the malignant component, have a favorable outcome [11][12][13][14]. The only neoplasms that are consistently graded in current practice are adenoid cystic carcinomas (AdCC), based on the growth pattern, mucoepidermoid carcinoma (MEC), with a combination of growth pattern and cytomorphological findings, and adenocarcinomas NOS, based on the degree of cellular atypia [1,8].…”
Section: Histological Gradingmentioning
confidence: 99%
“…The malignant component varies in phenotype and aggressiveness, i.e., from SDC to adenocarcinoma NOS, myoepithelial carcinoma, EMC, or AdCC, among others, or even with combined morphologies [11,13,14,56].…”
Section: Pa and Its Progression: An Example Of Recurrent Genetic Altementioning
confidence: 99%
“…The prognosis of salivary gland carcinomas in general depends on the disease stage, while the clinical outcome of ca-ex-PA also depends on the degree of invasion beyond the maternal PA (Seethala 2009;Antony et al 2012;Rito & Fonseca 2016;Williams et al 2017). While the extent of invasion associated with adverse outcome has been debated, intracapsular (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the false-negative CXPA cases had no consistent TIC or histological characteristics in the present study. The poor prognostic factors for CXPA reportedly included extracapsular extension of cancer components >2.5 mm from the capsule of the preexisting PA [6]. However, the detection of extracapsular extension using MR imaging can be very challenging; in fact, the morphology of the tumor margin and capsule was indistinguishable between CXPA and PA.…”
Section: Discussionmentioning
confidence: 99%